Strategi Qurrat Al-Kalam pada Pembelajaran Bahasa Arab dalam Meningkatkan Keterampilan Berbicara Siswa - Taufik Taufik; Faricha Ajeng Mega Utami; Nurul Aini; Mas’uliyyah; Nabila Priyanka Chafsoh; Nurul Arifah Imroniyah (Naskhi: Jurnal Kajian Pendidikan dan Bahasa Arab, 2023)
The lack of speaking skills among students at Madrasah Ibtidaiyah (MI) level is due to passive and less innovative learning, despite oral expression being a crucial aspect in learning Arabic. Consequently, this article aims to realize the implementation of the Qurrat Al-Kalam strategy to enhance students' speaking skills in Arabic subjects. This research utilizes qualitative methods in the form of literature studies, employing data spanning the last 10 years (2014-2023). Various relevant sources related to the discussion serve as references in this write-up. The data was subsequently analyzed using content analysis techniques. This strategy injects liveliness and dynamism into the classroom environment, presented in a manner resembling a ball game, effectively capturing students' attention and fostering their enthusiasm to achieve academic excellence. By necessitating students to formulate questions and determine answers based on their peers' inquiries, the strategy renders the learning process more active. The use of this strategy not only provides opportunities but also poses challenges for students to enhance their thinking potential and engagement in asking and answering. However, for optimal learning outcomes, it's essential for teachers to master the steps in implementing this strategy.